Photosynthetic response of ‘Maxi Gala’ apple trees covered with photoselective anti-hail nets - Mauta D.S. (2020)
© 2020 International Society for Horticultural Science. All rights reserved.The objective of this study was to evaluate the influence of photoselective anti-hail nets in the leaf content of photosynthetic pigments and in the photosynthetic response of ‘Maxi Gala’ apple trees. The experiment was carried out during the 2016/17 and 2017/18 growing seasons, in a commercial orchard located in Monte Alegre dos Campos city, Rio Grande do Sul State, Brazil. ‘Maxi Gala’ apple trees from an uncovered area (no netting), covered with black anti-hail net (standard hail net) and photoseletive anti-hail nets (yellow ChromatiNet®, blue ChromatiNet® and red ChromatiNet®) were used to determine the levels of carotenoids and chlorophylls, leaf area, specific leaf area and CO2 assimilation rate curves (A) in response to an increase of the photosynthetic photon flux density. The dispersion of blue and red light emitted by the red ChromatiNet® and blue ChromatiNet® photoseletive nets stimulated the maximum rate of CO2 assimilation in ‘Maxi Gala’ apple trees in response to an increase of photosynthetic photon flux density, under the climatic conditions of southern Brazil, favoring a better foliar photosynthetic efficiency.